2007
DOI: 10.1590/s1517-83822007000300015
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between genotypes and virulence factors in C. albicans strains isolated from vaginal secretion

Abstract: The physiopathogenesis of vulvovaginal candidiasis (VVC) is still not completely elucidated. The objective of this study was to evaluate if there is a relationship between the different genotypes of Candida albicans, their main agent and the virulence of this yeast in vaginal isolates, and to check if there are laboratorial markers that can predict the ability of each isolate to develop VVC independently of symptoms. The production of exoenzymes protease, phospholipase and haemolysin, resistance to hydrogen pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
2
2
1
1
Order By: Relevance
“…However, we could not establish a relationship between the genotypes and the virulence factors, or the genotypes and clinical infection. Earlier studies have reported similar findings (Shinobu et al, 2007;Abaci, 2011). …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, we could not establish a relationship between the genotypes and the virulence factors, or the genotypes and clinical infection. Earlier studies have reported similar findings (Shinobu et al, 2007;Abaci, 2011). …”
Section: Discussionsupporting
confidence: 76%
“…The results showed that genotype A was predominant in isolates from HIV-infected as well as -uninfected individuals. A higher incidence of genotype A among Candida genotypes has been reported previously (Sugita et al, 2002;Shinobu et al, 2007). However, we could not establish a relationship between the genotypes and the virulence factors, or the genotypes and clinical infection.…”
Section: Discussioncontrasting
confidence: 67%
“…In a similar study, Gharaghani et al reported genotype C (83.5%) as the most common genotype in vulvovaginal samples and those data were similar to our study 32 . In contrast with the published data of Shinobu et al, genotype A is the most common genotype in vulvovaginal samples 33 . Among the reports, the ratios of genotypes A, B, and C of C. albicans isolates varied.…”
Section: Discussionsupporting
confidence: 84%
“…These yeasts were isolated and identified in 2008 through classical 25 and molecular 26 methods and are part of a yeast bank maintained in the Medical Mycology Division of the Laboratory of Teaching and Research in Clinical Analysis at the State University of Maringá, Paraná, Brazil. The isolates have been stored in Sabouraud Dextrose Broth (SDB) (Difco, Detroit, MI) with 10% glycerol at -20°C since their identification.…”
Section: Microorganismsmentioning
confidence: 99%